Encysted hydrocele of the cord presenting as a groin swelling in an adult: a case report - Mahapatra, Bibekananda; Panchal, Anuradha; Mahadik, Abhishek; Chougle, Qurratulain (International Journal of Research in Medical Sciences, 2017)
The hydrocele of the cord presents as a translucent swelling in the inguinal canal or scrotum, separately above the testis. It is more commonly seen in childhood and is rare in adults. It comprises of two varieties based on their communication with the peritoneal cavity. The encysted hydrocele of the cord does not communicate with the peritoneal cavity above or the tunica vaginalis below. The other variety known as the funicular hydrocele communicates with the peritoneal cavity above but does not communicate with the tunica vaginalis below. This case report presents the case of a 22 year old young male with an inguinal swelling. Clinical differential diagnoses were of inguinal lymphadenitis, encysted hydrocele of the cord and irreducible hernia. The aim of this report is to highlight the role of ultrasonogram in early diagnosis and surgical excision as mainstay of treatment.